The efficiency of financing and R&D in technology-based SMEs and impact of financial regulation - Feng, Yongqi; Zhang, Haolin; Chiu, Yung-ho; Chang, Tzu-Han (Technological and Economic Development of Economy, 2022)
Technological innovation is a long-term activity with highly unpredictable returns on investment, which makes SMEs with information problems and lack of collateral value be vulnerable to financing constraints when engaging in innovation activities. This study incorporates financing and R&D activities into the evaluation of innovation efficiency and further considers the impact of financial regulation as an external factor in technology-based SMEs in China. This study puts forward a three-stage dynamic DDF-DEA model to explore the overall innovation efficiency as well as the efficiency of each stage in technology-based SMEs by dividing the innovation process into three stages, namely the financing stage, R&D stage and operating stage. The study reveals that the overall efficiency of innovation are higher in non-coastal areas of China than in coastal areas. Non-coastal regions have higher efficiency in the financing and operating stages, while coastal regions have higher efficiency in the R&D stage. Strengthening financial regulation could improve the financing and R&D efficiency both in coastal and non-coastal areas, but it has different effect on the operating efficiency in coastal and non-coastal areas. The results of this study could provide some reference for China and other emerging economies to formulate policies in improving the efficiency of financing and R&D.First published online 30 August 2022